THE AFFECTION AND CARE OF THE DEVELOPMENT OF CHILDREN WITH DISABILITIES IN CHILDREN EDUCATION - Pinheiro Wellichan, Danielle da Silva [UNESP]; Lucas Adurens, Fernanda Delai [UNESP] (Unesp-faculdade Ciencias & Letras, 2018)
Affection and care are important foundations in early childhood education and essential for the development of children with or without disabilities. Thus, the training of professionals from this initial period of basic education needs to be an issue on the agenda and focus of discussion. Encouraging this reflection in the school can play in favor of the inclusion of children from the early stages of school life. Therefore, the. following text seeks to discuss and propose reflections on actions that can be carried out in the context of Early Childhood Education to help a more humanized learning environment.
Keywords: Take care; Affection; Early Childhood Education; Special Education